Popular literature in Hindi and Urdu - Pritchett, Frances W., 1947- (Filmed by the Center for Research libraries for the South Asian Microfilm Project, 1993)
Collection on microfilm of South Asian popular literature in Hindi, Urdu, and related dialects. Consists primarily of qissah (narrative "chapbook" literature) and nautanki (folk-opera) texts, as well as other indigenous folk genres in prose and verse published from the late 19th Century to 1978.